Understanding grammar : parts of speech - Tangonan, Orlando L. (Malabon City : Mutya Publishing House, Inc., 2019)
This book is composed of thirteen lessons that deal with various communicative functions and specific grammatical forms that accompany them.
Unit 1. Word Formation -- Unit 2. The parts of speech -- Unit 3. Function/Structure words -- References.
Includes bibliographical references.
Keywords: ENGLISH LANGUAGE -- GRAMMAR